PENENTUAN UMUR YELLOW CAKE SECARA RADIOKRONOMETRI - Noerpitasari, Erlina; Fatimah, Syamsul; Haryati, Iis; Yanlinastuti, Yanlinastuti; Setiawan, Jan; Boybul, Boybul; Nugroho, Arif (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
YELLOW CAKE AGE DETERMINATION BY RADIOCHRONOMETRY. Radiochronometric dating of yellow cake has been carried out. The aim of this study was to obtain data on the age of yellow cake for compiling a database for nuclear forensics library. The radiochronometer used was 228Th/232Th. 232Th is thorium which naturally co-exists in yellow cake and will reach a decay equilibrium to 228Th. In the yellow cake production process, however, the equilibrium is disturbed so that the "time" will be zeroed again. The test samples were yellow cake from Cogema, from PTBGN mining in Kalan, and by-products from Petrokimia Gresik. The steps of processes include dissolving the sample, separating thorium from uranium by cation exchange chromatography using dowex 50W-X8 resin, electrodeposition of thorium and isotopes analysis using an alpha spectrometer. Age determination was performed by calculating the 228Th/232Th activity ratio and decay formula iteration. Based on the analysis of the 228Th and 232Th isotopes using an alpha spectrometer and the results of age calculations, the age of Cogema yellow cake was not able to be determined because it does not contain 232Th. The age of Petrokimia Gresik yellow cake is 9.90 years with a bias of 20.35 years and the age of PTBGN yellow cake is 12.85 years with a bias of more than 20.15 years when compared to the known estimated production time. The bias obtained is higher when compared to the results determined by previous researchers by the same method, i.e., a bias of less than 10 years.